Leaders as Role Models for the Voluntary Provision of Public Goods - Simon Gächter; Elke Renner (Institute for the Study of Labor (IZA), 2014)
We investigate the link between leadership, beliefs and pro-social behavior. This link is interesting because field evidence suggests that people's behavior in domains like charitable giving, tax evasion, corporate culture and corruption is influenced by leaders (CEOs, politicians) and beliefs about others' behavior. Our framework is an experimental public goods game with a leader. We find that leaders strongly shape their followers' initial beliefs and contributions. In later rounds, followers put more weight on other followers' past behavior than on the leader's current action. This creates a path dependency the leader can hardly correct. We discuss the implications for understanding belief effects in naturally occurring situations.
Keywords: C72; C90; H41; Z13; 330; leadership; beliefs; experiments; public goods; path dependency; public policy; management